Comparison of Sugammadex and Neostigmine in Terms of Time to Extubation in Pediatrics - Dilek Güzelce (Haseki Tıp Bülteni, 2016)
Aim: Sugammadex is a cyclodextrin compound which provides complete recovery of residual neuromuscular blockade. In this study, we compared sugammadex and neostigmine in terms of time to achieve a train-of-four (TOF) ratio of 0.9 and extubation time (TE). Methods: Thirty-seven patients, without lung disease and neuromuscular disease undergoing lower urinary tract surgery and inguinal hernia, were included in the study. Noninvasive arterial pressure, heart rate, pulse oximetry, and TOF-watch SX values were monitored during the surgery and, these parameters were recorded. After the surgery was completed, the patients were randomized into two groups: patients received either group neostigmine (group N) 0.05 mcg/kg and group sugammadex (group S) 2 mg/kg at reappearance of TOF ratio T2. Time to recovery to the TOF ratio of 0.9 (T0.9) and TE were compared between sugammadex and neostigmine Results: TE was found to be statistically longer in group N (6.06±2.47 minute) than in group S (4.30±2.48 minute) (p<0.041). Conclusion: We observed that sugammadex was more rapidly and effectively reversed the neuromuscular blockade compared to neostigmine. There were no serious adverse effects and significant hemodynamic changes in any measurement time. However, there is a limited number of studies on the safety and side effects of sugammadex in pediatric patients and additional data are needed to establish the safety in clinical practice.